Online Food Industry (A Study Case: Talabat) - Alsumait, Shahad; Alenezi, Rahaf (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Online food ordering has taken a huge place in the e-commerce sector, one of the essential parts of our daily lives. nowadays it is becoming the new way for the current generation especially with the new technology and the easy online access, people can easily order their food from any restaurant through a web page or an app. Creating a whole new market with a brand-new opportunity for entrepreneurs and for restaurants to reach the customers not only through actual restaurants where people go for food and services but to the comfort of their homes. Talabat is one of the biggest online food delivery company in the Middle East with more than 4000 different restaurants available for customers, as it grows and expands to 7 countries it faces a variety of problems that weakens the company’s share in the market allowing new entrants to have a competitive advantage and for talabat to lose customers. We’ll discuss some of this problem in the following report. Keywords: Talabat, e-commerce, online food delivery, restaurants, web business, customers.